Clinician Experiences and Attitudes Regarding Screening for Social Determinants of Health in a Large Integrated Health System - Schickedanz, Adam (Med Care, 2019)
BACKGROUND: Clinical screening for basic social needs –such as food and housing insecurity – is becoming more common as health systems develop programs to address social determinants of health. Clinician attitudes toward such programs are largely unexplored. OBJECTIVE: To describe the attitudes and experiences of social needs screening among a variety of clinicians and other health care professionals. RESEARCH DESIGN: Multi-center electronic and paper-based survey. SUBJECTS: Two hundred fifty-eight clinicians including primarily physicians, social workers, nurses, and pharmacists from a large integrated health system in Southern California. MEASURES: Level of agreement with prompts exploring attitudes toward and barriers to screening and addressing social needs in different clinical settings. RESULTS: Overall, most health professionals supported social needs screening in clinical settings (84%). Only a minority (41%) of clinicians expressed confidence in their ability to address social needs, and less than a quarter (23%) routinely screen for social needs currently. Clinicians perceived lack of time to ask (60%) and resources (50%) to address social needs as their most significant barriers. We found differences by health profession in attitudes toward and barriers to screening for social needs, with physicians more likely to cite time constraints as a barrier. CONCLUSIONS: Clinicians largely support social needs programs, but they also recognize key barriers to their implementation. Health systems interested in implementing social needs programs should consider the clinician perspective around the time and resources required for such programs and address these perceived barriers.